Cutaneous metastases secondary to colorectal carcinoma may not be as ominous as previously thought: a case report and review of the literature. (2nd July 2013) - Aravind, Biju; Kumar, Rohan; Basnyat, Pradeep
Abstract : Cutaneous metastasis is considered as an advanced presentation of colorectal cancer and mostly managed with palliative measures. We present a case report where such a case was radically treated with good result and review such reports published in literature. This shows a distinct subgroup that could benefit from such radical approach.